(untitled) (Communications in Mathematical Research, 2021)
In this paper, we study the multiplicity of positive solutions for a class of p-Laplacian difference equations with delay. We propose sufficient conditions for the existence of at least three positive solutions and we also provide two numerical examples to illustrate the theoretical results.